Design And Development Multilevel Inverterwith Different Modulation Index (MI) Based On Super Capacitor (SC) For Harmonic Reduction - Mohammed, Rasheed; Rosli, Omar; Marizan, Sulaiman (IDOSI Publications, 2016)
This paper presents a study on a three-phase five level Cascaded H-bridge multilevel inverter (CHBMLI) based on Newton-Raphson (NR) technique controller for optimization and non-optimization technique for harmonic reduction. The proposed system comprises of a DC source made up of super capacitor (SC) and the three phase five-level Cascaded H-bridge multilevel inverter (CHBMLI), with the controller based on Newton-Raphson (NR). The switching angle of the (CHB-MLI) with different modulation index MI has been calculated for optimization and non- optimization technique. The created source code programming is then stored in Digital Signal Processing (DSP) TMS320F2812. Experimental step-up has been conducted, whose results confirm the effectiveness of the proposed system in reducing Total Harmonic Distortion (THD) of the (CHBMLI) output.